Determinants of Environmental Disclosure. Does Leverage Matter? Reflection from Firms Listed in the Nairobi Security Exchange - Kipngetich, Tarus John; Tenai, Joel; Bonuke, Ronald (Journal of Accounting, Business and Finance Research, 2019)
This paper aimed to examine the effect of leverage on environmental accounting disclosure among the firms listed in the Nairobi Securities Exchange, Kenya. The research was guided by the stakeholder’s theory. The study adopted both explanatory and longitudinal research designs. The target population comprised of the 65 listed firms at Nairobi Securities Exchange from 2008 to 2017. However, inclusion criteria were the 27 listed firms consistently operating from 2008 to 2017 giving a total of 270 firm-year observations. The findings showed that leverage (β = -.16, ρ<.05) had a negative and significant effect on environmental disclosure in Kenyan listed firms. Similarly, the overall R2 showed a joint contribution of 17% of predictor variables that explain environmental accounting disclosure. The study concludes that leverage is a key predictor of environmental accounting disclosure. Firms listed at the Nairobi Securities Exchange ought to reduce debt financing so as to increase the level of environmental accounting disclosure.